PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK PEMBAYARAN E-MONEY TERHADAP KEPUASAN PELANGGAN PADA BATIK SOLO TRANS - Asngari, Rahma Nur Wahidahtun; Priyadi, Budi Puspo; Dwimawanti, Ida Hayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
A city needs transportation to help people in the city move from one place to another easily. Currently, there are many big cities in Indonesia, one of which is Surakarta City, which provides public transportation provided by the Surakarta City Governemnet called Batik Solo Trans (BST) consisting of various corridors with different road routes. At this time, Batik Solo Trans (BST) has provided convenience and comfort for the people of Surakarta City related to the innovative performance of its payment method, which is using an electronic card or emoney payment. This new payment method makes the payment transaction process faster because people only need to tap their electronic cards to the tap tool or scan the barcode available on the bus. However, there are indications that people feel dissatisfied with the emoney payments that are implemented because there are still various obstacles. The purpose of this research is to analyze the effect of service quality and product quality on customer satisfaction with the implementation of the e-money payment sysem in Batik Solo Trans (BST). Researchers will analyze through the theory of customer satisfaction, service quality, and porudct quality. The research method used in this research is a type of quantitavie research with data collection techniques through questionnaires. In determining research subjects, researchers will use convenience sampling techniques. The result of the research produced by researchers, namely the quality of e-money payment services partially has a significant influence on customer satisfaction with a value of 4.322. The quality of e-money payment product partially has a significant with a value of 4.315. Service quality and product quality of e-money payments together have a signicant influence on customer satisfaction with a value of 67.038.